CLAUSE STRUCTURE IN INDONESIAN POP SONG LYRICS: A SYNTACTIC STUDY - Rismayani Marpaung; Nazwa Umri Damanik; Lili Elisa Rahma; Tiara Sani; Siti Ismahani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This article examines clause structure in Indonesian pop song lyrics from a syntactic perspective using a literature review approach. Rather than conducting primary data analysis, the study synthesizes findings from journal articles, undergraduate theses, and empirical studies that focus on syntactic patterns in song lyrics. As a form of artistic discourse, pop song lyrics exhibit flexible linguistic characteristics and frequently diverge from canonical syntactic rules to accommodate aesthetic, expressive, and rhythmic demands. The synthesis reveals that Indonesian pop song lyrics predominantly employ simple clause structures, subject and object ellipsis, inversion, and fragmentary constructions. These syntactic patterns function to enhance emotional expression, maintain alignment with melodic structure, and increase memorability and listener engagement. The findings further indicate that syntactic realization in song lyrics occupies an intermediate position between spoken and written language, emphasizing functional and contextual meaning over formal grammatical completeness. This article provides a comprehensive overview of dominant clause structure characteristics in Indonesian pop song lyrics and discusses their implications for syntactic analysis, lyrical interpretation, and linguistic studies in popular music media. ABSTRAK Artikel ini mengkaji struktur klausa dalam lirik lagu pop Indonesia dari perspektif sintaksis melalui pendekatan tinjauan literatur. Penelitian ini tidak melakukan analisis data primer, melainkan mensintesis temuan dari artikel jurnal, skripsi, dan studi empiris yang membahas pola sintaksis dalam lirik lagu. Lirik lagu pop sebagai bentuk wacana artistik memiliki karakteristik kebahasaan yang cenderung fleksibel dan sering menyimpang dari kaidah sintaksis kanonik guna memenuhi tuntutan estetika, ekspresif, dan ritmis. Hasil sintesis menunjukkan bahwa lirik lagu pop Indonesia secara dominan menggunakan struktur klausa sederhana, elipsis subjek dan objek, inversi, serta konstruksi fragmentaris. Pola-pola sintaksis tersebut berfungsi untuk memperkuat ekspresi emosional, menjaga keselarasan dengan struktur melodi, serta meningkatkan daya ingat dan keterlibatan pendengar. Temuan ini juga menunjukkan bahwa realisasi sintaksis dalam lirik lagu menempati posisi antara bahasa lisan dan bahasa tulis, dengan penekanan pada fungsi komunikatif dan kontekstual. Artikel ini memberikan gambaran komprehensif mengenai karakteristik struktur klausa dalam lirik lagu pop Indonesia serta implikasinya bagi kajian sintaksis, interpretasi lirik, dan studi kebahasaan dalam media musik populer.